Economic and Nutritional Transformation of Coastal Communities Based on Seaweed - Nurhidayati Islamiah; Nurul Hikmah; Andi Rifqah Purnama Alam; Afriyani Afriyani (Journal of Business Management and Economic Development, 2026)
This study examines the low contribution of seaweed development to the welfare of coastal households, which has long been export-oriented and focused on raw material production with limited added value. This condition has meant that seaweed has yet to deliver a significant impact on income stability, food security, and nutritional quality. This study aims to analyze how seaweed-based economic transformation can improve household welfare through the linkages between economic, food, and nutrition systems. The study uses household survey data from coastal areas of South Sulawesi, Indonesia, employing a structural econometric model approach to examine the direct and indirect relationships between value-added processing, technology access, market integration, income stability, food security, consumption diversity, and nutritional status. The findings indicate that seaweed-based economic transformation can significantly improve welfare when supported by value-added product development, technology utilization, and broader market access. Income stability and market integration serve as the primary mechanisms linking economic activity to improvements in food security and nutritional quality. The study concludes that seaweed needs to be positioned as a strategic instrument for inclusive and sustainable coastal development, rather than merely an export commodity. These findings provide an empirical basis for formulating policies that integrate marine economic transformation with food and nutrition security. This study contributes the literature on coastal development and the blue economy by providing an integrated analytical framework that links seaweed-based economic transformation with food security, nutritional outcomes, and human resource development at the household level, extending existing research beyond commodity- and export-oriented perspectives.